2021
DOI: 10.3389/fpsyg.2021.718172
|View full text |Cite
|
Sign up to set email alerts
|

Real and Imagined Smellscapes

Abstract: The smellscape is the olfactory environment as perceived and understood, consisting of odours and scents from multiple smell sources. To what extent can audiovisual information evoke the smells of a real, complex, and multimodal environment? To investigate smellscape imagination, we compared results from two studies. In the first, onsite participants (N = 15) made a sensory walk through seven locations of an open-air market. In the second, online participants (N = 53) made a virtual walk through the same locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…The specific on-site context will limit the scene, thus making the results more targeted. In addition, previous study has found that audio–visual information can also evoke specific smellscape imagination, and consequently the influence of imagination on multimodal perception should not be underestimated (Lindborg and Liew, 2021). The results of this study showed that the number of odour environment evaluation indicators affected by sound was less than the number of the sound environment evaluation indicators affected by odour and to a lesser extent, indicated that the influence of odour on sound perception was stronger than the influence of sound on odour perception.…”
Section: Discussionmentioning
confidence: 99%
“…The specific on-site context will limit the scene, thus making the results more targeted. In addition, previous study has found that audio–visual information can also evoke specific smellscape imagination, and consequently the influence of imagination on multimodal perception should not be underestimated (Lindborg and Liew, 2021). The results of this study showed that the number of odour environment evaluation indicators affected by sound was less than the number of the sound environment evaluation indicators affected by odour and to a lesser extent, indicated that the influence of odour on sound perception was stronger than the influence of sound on odour perception.…”
Section: Discussionmentioning
confidence: 99%
“…Such linkages of odor description and perceived sources are considered "typical" and have been attributed to ecological conditioning-the immediate and automatic tendency to associate a source with an odor sensation. 84…”
Section: Characteristics Of Osac: the Metrovan Smellscapementioning
confidence: 99%
“…Groups of five smellwalkers undertook field work comparing live or simulated experience (using audio and video recordings) of Singaporean open air markets ( Lindborg and Liew 2021 ). Locations were selected for having strong sensory experience identity, with duration between 70 and 90 min in the early morning, covering seven stopping points.…”
Section: Introductionmentioning
confidence: 99%
“…Attributes included the evaluation of olfactory site aspects on a seven-point scale as well as personal descriptions of thoughts and feelings. Interestingly, participants were asked to describe the most faint or secretive, most loud or dominant, most beautiful or precious, and the most ugly or disgusting smell detected in each location, in conjunction with perceived sources or events ( Lindborg and Liew 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation